Food price changes and consumer welfare in Ghana in the 1990s - Charles Ackah; Simon Appleton (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
In this paper, we analyse the effect of food price changes on household consumption in Ghana during the 1990s and assess the extent to which changes can be explained by trade and agricultural policy reforms. The measurement of the total household welfare effect, one that jointly considers (static) first order effects as well as (dynamic) consumption responses, is the object of this study. Food consumption behaviour in Ghana is analyzed by estimating a complete food demand system using the linear approximate version of the AIDS model with household survey data for 1991/92 and 1998/99. The estimated price elasticities are then utilized to evaluate the distributional impacts of the relative food price changes in terms of compensating variation. The results indicate that the distributional burden of higher food prices fell mainly on the urban poor. While it is difficult to attribute the price changes and by implication the welfare losses, to any particular policy per se, a simulation analysis indicates that trade liberalisation may not have been responsible for the welfare losses. Our simulation exercise suggests that further tariff liberalisation would tend to offset the welfare losses for all households although it is the poor and rural consumers who stand to gain the most.
Keywords: D12; O12; O55; Q18; 330; Food prices; Demand analysis; Consumer behaviour; Welfare; Ghan; Nahrungsmittelpreis; Nahrungsmittelkonsum; Nachfragesystem; Privater Haushalt; Ghana